Evaluasi dan Optimalisasi Penyediaan Air Bersih Berbasis Masyarakat (Studi Kasus: Kawasan Langara Pesisir, Kab. Konawe Kepulauan) - Darmawan, Ilham Kari; Mangidi, Uniadi; Muriadin, Muriadin; Balaka, Rudi (Universitas Sulawesi Tenggara, 2024)
The Langara Coastal area is the economic center area of the capital city of Konawe Islands Regency. However, the provision of clean water as a basic need is still not fulfilled, this is because the source of clean water in the Langara Coastal Area currently still depends on Community Self-Help, as a result, water distribution is carried out in shifts. This research aims to determine air needs, the condition of the existing distribution network, and optimize the clean water distribution system. Air requirements are calculated using an analysis of population projections for 15 years. Analysis of pipe hydraulics using EPANET 2.2 Software, and air flow by gravity using PVC pipes. The analysis results show that the population in 2036 will be 1816 people with peak hour water demand of 4.13 l/sec. The condition of the existing distribution network shows that all Junctions have an average pressure of 9 atm. Meanwhile, the pipe with the highest speed at P3 is 0.47 m/s and the speed at P15 is 0.04 m/s, indicating that the existing conditions do not meet the technical criteria of Minister of PUPR Regulation No. 27/PRT/M/2016. So to increase the flow speed it is necessary to change the pipe dimensions at several points. In peak hour optimization simulations, the maximum speed occurs in pipes P2, P3, P4, and P10, namely 2.61 m/s, while the lowest speed occurs in pipe P21, namely 0.30 m/s. The results of this optimization are by the speed criteria in Minister of PUPR Regulation No.27/PRT/M/2016